Pengukuran Topografi Ketinggian: Studi Kasus Menggunakan Metode Real-Time Kinematic (RTK) GPS Geodetik R6 - Prayogo, Luhur Moekti; Muhsoni, Firman Farid (Universitas Trunojoyo Madura, 2024)
Large-scale topographic information is often difficult to obtain accurately. Technological advances in the field of surveying provide sophisticated instruments with varying degrees of accuracy. One of the widely used instruments is the Global Positioning System (GPS) Geodetic R6, which has an accuracy of up to 5-10 mm and the ability to capture L1 and L2 signals. This research aims to conduct altitude topography mapping using GPS Geodetic R6 in the coastal area of Kamal, Bangkalan Regency, Madura. The method used is Real-Time Kinematic (RTK) with a configuration of two base stations. The first base is located at Trunojoyo University Park Madura (coordinates: S 7°07'44.99587“, E 112°43'23.81230”, elevation: 6.81 meters), while the second base is located in front of Jalan Raya Telang Church (coordinates: S 7°07'46.65292“, E 112°42'46.91250”, elevation: 3.40 meters). The measurement results show that the average elevation in Telang Village, Kamal District, ranges from 3.29 to 7.89 meters with a Root Mean Square Error (RMSE) of 3.65. This research confirms that the R6 Geodetic GPS has high accuracy capabilities in topographic measurements, making it very reliable for precision mapping of coastal areas. This finding makes a significant contribution in supporting various development and mitigation needs in coastal areas.